ANALISIS YURIDIS TINDAK PIDANA CYBERCRIME DALAM PERBUATAN PIDANA PENCEMARAN NAMA BAIK DITINJAU DARI UNDANG-UNDANG NO. 8 TAHUN 2011 TENTANG INFORMASI TRANSAKSI DAN ELEKTRONIK DAN HUKUM PIDANA - Abdurrahman Harit’s Ketaren; Syafruddin Kalo; Marlina Marlina; Jelly Leviza (Universitas Sumatera Utara, 2018)
Abstract This internet development is indeed extraordinary. The rapid development of Internet technology has also spawned new crimes in the field, such as the crime of data manipulation, espionage, sabotage, provocation, deprivation, hacking, software theft and hardware damage, defamation, cyberbullying and various other things. Then the title of this research is